Partisipasi Warga Sekolah Dalam Upaya Pelaksanaan Program Adiwiyata Di SDN Tembok Dukuh IV/8 Surabaya - Afifah Diah Pitaloka; Hariyoko, Yusuf (Faculty of Social and Political Science, 2023)
Not all schools around us have a high level of sanitation and enviromental awareness, it can be seen from school conditions that are not very clean; garbage is scattered and not sorted, smelly and dirty bathrooms, also dry and unkempt plants. Therefore, since 2006 Ministry of Environment carried out Adiwiyata Program which aims to intensify the concern of schools and enviromental culture. So as with SDN Tembok Dukuh IV/86 Surabaya endeavor to always intensify the awareness about the schools concern, so the participation of all school residents is needed to embody Adiwiyata Program. The purpose of this research is to find out what programs are running and does all the school residents involve in running the programs. This research uses qualitative descriptive method with interview, observation, and documentation study as the data collection techniques. The result of this research is a lot of programs are carried out to support Adiwiyata Program and not all school residents participate in the programs at one time due to teachers and school staff have their own bustles, but there are several students don't participate because of the lack of enviromental awareness.